Does e-commerce participation affect green agrotechnology adoption among reservoir resettlers? The case of China’s Three Gorges Reservoir area - Zhao, Xu; Cui, Zhuo; Zhao, Feifei (Frontiers in Environmental Science, 2022)
This study sought to explore the impact of e-commerce participation on resettlers’ green agrotechnology adoption and help rural revitalization and ecological product value realization in the Three Gorges Reservoir area. Firstly, we combined the theory with an induced innovation model and then introduced the risk perception factor into the expected utility theory. A model of resettler green agrotechnology adoption under different levels of e-commerce participation was constructed, and the research hypotheses were proposed accordingly. The survey data of resettlement growers in Zigui, the first county of the Three Gorges Reservoir area, were used as a sample to carry out an empirical test with the ordered-probit model. The results showed that e-commerce participation behavior significantly and positively affected the level of green agrotechnology adoption at the 1% level, and the ecological value expectation of agricultural products and the agrotechnology support provided by e-commerce were important driving factors. There were variations in the effects of different modes of e-commerce participation on agrotechnology adoption. Risk-averse behavior of resettlers can weaken the effect of e-commerce participation on agrotechnology adoption.